Jurisdiction and powers of the civil courts - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2014)
The Courts of Justice in Malaysia comprises the the superior courts and the subordinate courts. The superior courts are composed of the Federal Court (the apex court), the Court of Appeal, and the two High Courts of coordinate jurisdiction and status, namely the High Court of Malaya for Peninsular Malaysia and the High Court of Sabah and Sarawak, for the States of Sabah, Sarawak and Labuan. The jurisdiction and powers of these courts are provided in the Courts of Judicature Act 1964. Meanwhile, the subordinate courts consist of the Sessions Court and the Magistrates’ Court. The jurisdiction and powers of these courts areprovided in the Subordinate Courts Act 1948. This chapter discusses the jurisdiction and powers of the ordinary courts of law or civil courts in Malaysia. Further, the Court For Children constituted under the Child Act 2001 which hears cases on charges pressed against children is also discussed in this chapter. It is noteworthy that if the accused person falls under the definition of a ‘child’ in s. 2 of the Child Act 2001, which in general is between the age of 12 to 18, he/she will be tried for offences under the Penal Code in accordance with the Child Act 2001